Impact of Irrgation on Land Utilisatin and Cropping - Malhotra, S P; Bharara, L P; Patwa, F C (Annals of Arid Zone, 2016)
With the introduction of irrigation and its increasing, potential. available in R.C.P Tehsil Gharsana, dist. Bijaynagar the area under irrigation has' increased from 0.45% in 1967-68 to 12.22% in 1969-70: There is lib overall increase of 5.64%'in the net area sown within -the above period of three years. The introduction of irrigation is gradually changing the cropping pattern from subsistence farming to commercial farming. The various kharif crops introduced are maize, jowar; rice; urad, and arhar, in the .Tehsil. Even after irrigation bajra and moong remained the chief cereal and pulse crops. The chief rabi food crops introduced in the region are wheat (among cereals), Masoor,(pulse), Alsi and Raee (oil seeds) and Barseem (Fodder crop). Sar80n and Tarameera remained the chief oil seed crops even after irrigation. The multiple crops grown and introduced have made an intensive use of land thus increasing the intensity of cropping in the region. However most of the actual irrigation potential available remained unutilised because of the non or untimely allotment of lands by the R. C: P. Tehsil authorities; non or untimely vaiIabi1ity of water for irrigation; non-construction of the field irrigation channels from the 'main canal and delay by the allottees in improvement of the new lands bringing them, under cultivation.